Size matters: the effects of ontogenetic disparity on the phylogeny of Trematopidae (Amphibia: Temnospondyli). Issue 1 (20th February 2020) - Gee, Bryan M
Abstract: Trematopids are a clade of terrestrial Permo-Carboniferous temnospondyl amphibians. The intrarelationships of this clade are poorly known. This is largely attributable to a substantial disparity in size between type specimens, which range from the small-bodied lectotype of Mattauschia laticeps (< 4 cm skull length) to the large-bodied holotype of Acheloma cumminsi (> 15 cm skull length). Inferred correlation of size disparity with ontogenetic disparity has led previous workers either to omit taxa in phylogenetic analyses or to forgo an analysis altogether. Here, I take a specimen-level approach and multiple subsampling permutations to explore the phylogeny of the Trematopidae as a case study for assessing the effects of ontogenetic disparity on phylogenetic reconstruction in temnospondyls. The various analyses provide evidence that ontogenetic disparity confounds the phylogenetic inference of trematopids but without a directional bias. Tree topologies of most permutations are poorly resolved and weakly supported, reflecting character conflict that results from the inability of the analyses to differentiate retained plesiomorphies from juvenile features. These findings urge caution in the interpretation of phylogenetic analyses for which ontogenetic disparity exists, but is unaccounted for, and provide a strong impetus for more directed exploration of the interplay of ontogeny and phylogeny across Temnospondyli.